Flame-retardant anti-dripping TPU (thermoplastic polyurethane) film and preparation method thereof
By using cage polysilsesquioxane and acid modified montmorillonite as flame retardant fillers in the TPU film, the problem of poor flame retardant and droplet resistance performance of TPU film is solved, achieving better flame retardant and droplet resistance effect, while simplifying the process and reducing costs.
Patent Information
- Application Number
- CN202411757755.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The TPU film has poor flame retardant and droplet resistance. The existing coating process has poor flame retardant effect and is not environmentally friendly. The cost of adding flame retardant is high and the effect depends on dispersion uniformity.
Cage polysilsesquioxane and acid-modified montmorillonite are used as flame retardant fillers to form flame retardant and shielding layers in the TPU film through their unique structure and properties, preventing molecular movement and small molecules from escaping, improving flame retardant performance and anti-droplet effect.
It significantly improves the flame retardant performance and anti-droplet effect of the TPU film, reduces the softened fluidity, enhances the protection and shading ability of the film material, and has a simple process and relatively low cost.
Abstract
Description
Technical Field
[0001] The present application relates to a polyurethane material, and more specifically, to a flame retardant and anti-drip TPU film and a preparation method thereof. Background Art
[0002] TPU, or thermoplastic polyurethane elastomer, is a polymer material with properties between rubber and plastic. It has high strength, high toughness, wear resistance, oil resistance and other properties. It is widely used in defense, medical, food and other industries. TPU films made by calendering, casting, film blowing, coating and other processes can be used in smart wearables, outdoor products and other scenarios, but TPU itself is easy to burn, and it is accompanied by combustible droplets when burning, which adhere to combustibles and accelerate the spread of fire, causing greater harm to life and property. The flame retardant effect of the flame retardant film prepared by the coating process is poor and not environmentally friendly. Adding flame retardants during the film stretching process to improve the flame retardancy of the TPU film is low-cost, but the amount of flame retardant added is large, and the flame retardant effect is very dependent on the uniformity of the dispersion of the flame retardant in the film. How to provide a TPU film with good flame retardancy and anti-droplet is of great significance. Summary of the invention
[0003] In order to solve the problem that the flame retardant and anti-dripping properties of TPU film are poor, the present application provides a flame retardant and anti-dripping TPU film and a preparation method thereof.
[0004] In a first aspect, the present application provides a flame retardant and anti-drip TPU film, comprising the following raw materials in parts by weight: 80-100 parts of TPU particles, 10-12 parts of flame retardant, 12-20 parts of flame retardant filler, and 0.01-1 part of cellulose nanocrystals, wherein the flame retardant filler comprises cage-type polysilsesquioxane and acid-modified montmorillonite.
[0005] Cage-type polysilsesquioxane, or POSS, dilutes the concentration of combustible gas on the surface of the TPU film by burning itself and forms a silicon oxide layer on the film to inhibit heat transfer, achieving a certain flame retardant effect and improving the flame retardant properties of the TPU film. At the same time, POSS has a unique cage structure and can form a strong hydrogen bond with the polyurethane matrix, which works together to delay the movement of the molecular chain and the escape of small molecules, thereby hindering the melting drop of the TPU film after heating. Montmorillonite is a sheet-like silicate with a negative charge on the surface. It has strong adsorption capacity and dispersion properties and can produce good barrier properties. By adding a certain amount of montmorillonite, the entry of combustible gas is hindered, the flame retardant properties of the TPU film are improved, and the obtained TPU film is blocked at the same time, the fluidity after softening is reduced, and the anti-melting drop effect is improved. By acid-modifying montmorillonite, the modified montmorillonite has a larger specific surface area, better adsorption and chemical activity, and is tightly adsorbed inside the obtained TPU film for blocking. By using cage-type polysilsesquioxane and lamellar acid-modified montmorillonite together as flame-retardant fillers, the barrier properties of the prepared film material are good, and the flame retardant and anti-melting droplet performance is better. Cellulose nanocrystals are a kind of nano-scale cellulose extracted from natural fibers, which has high strength and can form a certain interpenetration effect in the TPU film. They also have good affinity for the polyurethane matrix and the flame-retardant filler of the present application, and play the effect of weakening the local stress of the interface. Under the action of stress, they can slide along the surface of the flame-retardant filler, and the broken bonds are reconnected into new bonds. By adding a certain mass of cellulose nanocrystals, the bonding strength of the flame-retardant filler and the polyurethane matrix can be improved, and the cage-type polysilsesquioxane and the acid-modified montmorillonite are interpenetrated with the polyurethane matrix more closely, and combustible gases are not easy to enter. The components in the film are closely adsorbed and connected together, and the protection and shielding effect on the TPU film is stronger, and the flame retardant and anti-melting droplet effect of the prepared TPU film is better.
[0006] In a specific embodiment, the preparation steps of the acid-modified montmorillonite include: washing the montmorillonite, drying it, then adding it to a 2-4% volume concentration phosphoric acid solution, stirring it evenly, filtering it, washing it, and drying it to obtain the acid-modified montmorillonite.
[0007] By adopting the above scheme, the acid modification step is relatively simple, the obtained montmorillonite has a large specific surface area, and the adsorption effect on the components in the TPU film is better. At the same time, the acid modification process will not damage the structure of the montmorillonite much. The modified montmorillonite can achieve better adsorption and barrier effects at the same time.
[0008] In a specific embodiment, the cage polysilsesquioxane is octaphenyl octasilsesquioxane.
[0009] During the production process, the applicant found that under the component settings and weight portions of the present application, the flame retardant and anti-dripping TPU prepared using octaphenyl octasilsesquioxane as a flame retardant filler has better flame retardant and anti-dripping effects. It may be that the flame retardant and anti-dripping TPU film prepared at this time has a certain rigidity. Therefore, the addition of octaphenyl octasilsesquioxane as a flame retardant filler achieves better dispersion in the film, making the flame retardant effect of the prepared TPU film better. At the same time, the surface of octaphenyl octasilsesquioxane has more electron-withdrawing groups, and after being used together with the negatively charged montmorillonite on the surface as a flame retardant filler, the two form a closer connection, so that the cage-type octaphenyl octasilsesquioxane and the lamellar montmorillonite work together, and the shielding and blocking effects on the prepared TPU film are good, and the flame retardant and anti-dripping performance of the prepared TPU film is better.
[0010] In a specific embodiment, the flame retardant filler is premixed with the cellulose nanocrystals.
[0011] By adopting the above scheme, the premixed cellulose nanocrystals can evenly slide and distribute on the surface of the flame retardant filler, and can also connect the defects on the surface of the flame retardant filler. After the flame retardant filler and the cellulose nanocrystals are premixed, the connection between the flame retardant filler and the flame retardant and anti-dripping TPU film is more uniform and tight, and the flame retardant and anti-dripping performance is better.
[0012] In a specific embodiment, the mass ratio of octaphenyl octasilsesquioxane to acid-modified montmorillonite is (2-2.3):1.
[0013] At this mass ratio, octaphenyl octasilsesquioxane and acid-modified montmorillonite are evenly dispersed, with the best flame retardant, adsorption and shielding effects, and the resulting TPU film has good flame retardant and anti-dripping properties.
[0014] In a specific embodiment, the mass ratio of the flame retardant filler to the cellulose nanocrystals is (15-20):1.
[0015] By adopting the above scheme, the cellulose nanocrystals have a good connection effect between the flame retardant filler and the TPU film.
[0016] In a specific embodiment, the mass ratio of the flame retardant filler to the cellulose nanocrystals is (16-17):1.
[0017] By adopting the above scheme, the connection effect of cellulose nanocrystals between the flame retardant filler and the TPU film is the best, the prepared TPU film is dense and not easy to melt and drip, the added cellulose nanocrystals are less in weight, and the flame retardant effect is good.
[0018] In a second aspect, the present application provides a method for preparing a flame retardant and anti-drip TPU film, comprising the following steps:
[0019] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0020] S2: melt-blending, cooling, granulating and casting the mixed materials to obtain a flame-retardant and anti-drip TPU film.
[0021] The preparation method of the above technical solution has a simple process and is suitable for the component composition of the flame-retardant and anti-melting-drip TPU film of the present application. The components inside the prepared film material are tightly connected and have a good flame-retardant and anti-melting-drip effect.
[0022] In a specific embodiment, the melting temperature is 200-210°C, and the casting temperature is 180-200°C.
[0023] By adopting the above scheme, the extrusion temperature is suitable for the film material raw material of the present application, the molding process is stable, the residual stress is small, the surface strength of the prepared film material is uniform, the flame retardant and the flame retardant filler are evenly distributed, and the performance is good.
[0024] In summary, this application has the following beneficial effects:
[0025] 1. The present application adds a certain amount of cage-type polysilsesquioxane and acid-modified montmorillonite to polyurethane for joint flame retardancy, and utilizes the cage-type structure of cage-type polysilsesquioxane and the lamellar structure of acid-modified montmorillonite to hinder molecular motion and delay the dripping of TPU film under heat.
[0026] 2. In the present application, by limiting the cage-type polysilsesquioxane to octaphenyl octasilsesquioxane and limiting the mass ratio of the cage-type polysilsesquioxane to the acid-modified montmorillonite, the electron-withdrawing octaphenyl octasilsesquioxane and the surface negatively charged acid-modified montmorillonite are more closely connected between the polyurethane, and the two work together to provide flame retardant and steric hindrance effects, thereby significantly improving the flame retardant and anti-dripping properties of the polyurethane.
[0027] 3. The present application premixes cellulose nanocrystals with fillers and limits the mass ratio of the two, so that the cellulose nanocrystals are more evenly and concentratedly adsorbed on the surface of the filler, fills the defects of the filler and improves the compatibility of the filler with the polyurethane system, and achieves better interpenetration with the polyurethane system, thereby better exerting the flame retardant and anti-melting dripping effect of the filler on the prepared TPU film. DETAILED DESCRIPTION
[0028] The following is a more specific description of the technical solution of the present invention in combination with several specific implementation examples. The embodiments are only partial embodiments of the present invention, not all of them. The following specific embodiments can be combined with each other, and the same or similar concepts or processes therein may not be repeated in some embodiments.
[0029] Unless otherwise specified, the experimental reagents in the preparation examples, embodiments and comparative examples are all conventional commercial brands or obtained through conventional preparation processes.
[0030] In the preparation examples, embodiments and comparative examples: octamethyl octasilsesquioxane was purchased from Hubei Xinhongli Chemical XHL1862, hereinafter referred to as octamethyl POSS; octaphenyl octasilsesquioxane was purchased from Zhengzhou Alpha Chemical A256791, hereinafter referred to as octaphenyl POSS; flame retardant was purchased from Bailing Biotech FR191.
[0031] Preparation Example
[0032] Preparation Example 1: Acid-modified montmorillonite.
[0033] 200 g of montmorillonite was filtered with deionized water for 3 times, dried, added into 800 ml of 3% VT phosphoric acid solution, stirred at 25° C. for 20 minutes, filtered, and washed with deionized water for 4 times to obtain acid-modified montmorillonite.
[0034] Preparation Example 2: Acid-modified montmorillonite.
[0035] 200 g of montmorillonite was filtered with deionized water for 3 times, dried, added into 800 ml of 5% vt phosphoric acid solution, stirred at 25° C. for 20 minutes, filtered, and washed with deionized water for 4 times to obtain acid-modified montmorillonite.
[0036] Preparation Example 3: Acid-modified mica powder.
[0037] 200 g of mica powder was filtered with deionized water for 3 times, dried, added into 800 ml of 3% vt phosphoric acid solution, stirred at 25° C. for 20 minutes, filtered, and washed with deionized water for 4 times to obtain acid-modified mica powder.
[0038] Example
[0039] Example 1
[0040] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 40 g of octamethyl POSS, 40 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0041] The preparation method of flame retardant anti-drip TPU film is as follows:
[0042] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0043] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0044] Example 2
[0045] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 500 g of TPU particles, 60 g of flame retardant, 30 g of octamethyl POSS, 50 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0046] The preparation method of flame retardant anti-drip TPU film is as follows:
[0047] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0048] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0049] Example 3
[0050] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 450 g of TPU particles, 55 g of flame retardant, 40 g of octamethyl POSS, 40 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0051] The preparation method of flame retardant anti-drip TPU film is as follows:
[0052] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0053] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0054] Example 4
[0055] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 40 g of octamethyl POSS, 40 g of acid-modified montmorillonite obtained in Preparation Example 2, and 0.05 g of cellulose nanocrystals.
[0056] The preparation method of flame retardant anti-drip TPU film is as follows:
[0057] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0058] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0059] Example 5
[0060] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 40 g of octamethyl POSS, 40 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0061] The preparation method of flame retardant anti-drip TPU film is as follows:
[0062] S0: Dry the raw material components separately, then weigh the octamethyl POSS, the acid-modified montmorillonite obtained in Preparation Example 1, and the cellulose nanocrystals according to their mass, and mix them evenly to obtain a premix;
[0063] S1: adding the premix to TPU particles, then adding a flame retardant, and mixing evenly to obtain a mixture;
[0064] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0065] Example 6
[0066] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 40 g of octaphenyl POSS, 40 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0067] S0: Dry the raw material components separately, then weigh the octamethyl POSS, the acid-modified montmorillonite obtained in Preparation Example 1, and the cellulose nanocrystals according to their mass, and mix them evenly to obtain a premix;
[0068] S1: adding the premix to TPU particles, then adding a flame retardant, and mixing evenly to obtain a mixture;
[0069] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0070] Example 7
[0071] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 54 g of octaphenyl POSS, 26 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0072] S0: Dry the raw material components separately, then weigh the octamethyl POSS, the acid-modified montmorillonite obtained in Preparation Example 1, and the cellulose nanocrystals according to their mass, and mix them evenly to obtain a premix;
[0073] S1: adding the premix to TPU particles, then adding a flame retardant, and mixing evenly to obtain a mixture;
[0074] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0075] Example 8
[0076] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 56 g of octaphenyl POSS, 24 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0077] S0: Dry the raw material components separately, then weigh the octamethyl POSS, the acid-modified montmorillonite obtained in Preparation Example 1, and the cellulose nanocrystals according to their mass, and mix them evenly to obtain a premix;
[0078] S1: adding the premix to TPU particles, then adding a flame retardant, and mixing evenly to obtain a mixture;
[0079] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0080] Example 9
[0081] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 52 g of octaphenyl POSS, 28 g of acid-modified montmorillonite obtained in Preparation Example 1, and 0.05 g of cellulose nanocrystals.
[0082] S0: Dry the raw material components separately, then weigh the octamethyl POSS, the acid-modified montmorillonite obtained in Preparation Example 1, and the cellulose nanocrystals according to their mass, and mix them evenly to obtain a premix;
[0083] S1: adding the premix to TPU particles, then adding a flame retardant, and mixing evenly to obtain a mixture;
[0084] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0085] Example 10
[0086] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 54 g of octaphenyl POSS, 26 g of acid-modified montmorillonite obtained in Preparation Example 1, and 5 g of cellulose nanocrystals.
[0087] S0: Dry the raw material components separately, then weigh the octamethyl POSS, the acid-modified montmorillonite obtained in Preparation Example 1, and the cellulose nanocrystals according to their mass, and mix them evenly to obtain a premix;
[0088] S1: adding the premix to TPU particles, then adding a flame retardant, and mixing evenly to obtain a mixture;
[0089] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0090] Embodiment 11
[0091] The flame-retardant and anti-drip TPU film of this embodiment uses the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 54 g of octaphenyl POSS, 26 g of acid-modified montmorillonite obtained in Preparation Example 1, and 4 g of cellulose nanocrystals.
[0092] S0: Dry the raw material components separately, then weigh the octamethyl POSS, the acid-modified montmorillonite obtained in Preparation Example 1, and the cellulose nanocrystals according to their mass, and mix them evenly to obtain a premix;
[0093] S1: adding the premix to TPU particles, then adding a flame retardant, and mixing evenly to obtain a mixture;
[0094] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0095] Comparative Example
[0096] Comparative Example 1
[0097] The flame-retardant and anti-drip TPU film of this comparative example adopts the following raw materials by weight: 550 g of TPU particles, 55 g of flame retardant, 80 g of octamethyl POSS, and 0.05 g of cellulose nanocrystals.
[0098] The preparation method of flame retardant anti-drip TPU film is as follows:
[0099] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0100] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0101] Comparative Example 2
[0102] The flame-retardant and anti-drip TPU film of this comparative example adopts the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 40 g of octamethyl POSS, 40 g of acid-modified mica powder obtained in Preparation Example 3, and 0.05 g of cellulose nanocrystals.
[0103] The preparation method of flame retardant anti-drip TPU film is as follows:
[0104] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0105] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0106] Comparative Example 3
[0107] The flame-retardant and anti-drip TPU film of this comparative example adopts the following raw materials by weight: 400 g of TPU particles, 50 g of flame retardant, 40 g of octamethyl POSS, and 40 g of acid-modified montmorillonite obtained in Preparation Example 2.
[0108] The preparation method of flame retardant anti-drip TPU film is as follows:
[0109] S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture;
[0110] S2: The mixed material is melt-blended at 200° C., cooled, granulated, and tape-casted at 180° C. to obtain a flame-retardant and anti-drip TPU film.
[0111] Performance testing
[0112] Test 1: The flame retardant effect of the flame retardant and anti-drip TPU films prepared in the examples and comparative examples was tested with reference to the UL94 standard.
[0113] Test 2: Refer to the standard "GB240984" (flame retardant performance test method - vertical combustion method), fix the sample at a position 30.0cm away from the base, and place 0.5cm thick absorbent cotton on the base. Use the fire source to act on the bottom of the sample for 10 seconds continuously, wait for the sample to extinguish, and then act for 10 seconds, record the experimental phenomenon, and divide it into five levels of 1-5 according to the degree of dripping, where 1 is no dripping at all and 5 is severe dripping.
[0114] The results are summarized in Table 1.
[0115] Table 1 Flame retardant effect Droplet level Example 1 Go out within 30 seconds 3 Example 2 Go out within 30 seconds 3 Example 3 Go out within 30 seconds 3 Example 4 Go out within 30 seconds 4 Example 5 Go out within 30 seconds 2 Example 6 Go out within 30 seconds 2 Example 7 Goes out within 10 seconds, does not exceed 125mm line 2 Example 8 Goes out within 10 seconds, does not exceed 125mm line 2 Example 9 Goes out within 10 seconds, does not exceed 125mm line 2 Example 10 Fire will extinguish 1 Embodiment 11 Goes out within 10 seconds, does not exceed 125mm line 1 Comparative Example 1 Keep burning 5 Comparative Example 2 Keep burning 4 Comparative Example 3 Keep burning 4
[0116] In combination with Examples 1-3, Comparative Examples 1-3 and Table 1, the present application adds a certain amount of cage-type polysilsesquioxane and acid-modified montmorillonite to polyurethane to obtain a TPU film with good flame retardant effect and improved anti-melting dripping effect;
[0117] In combination with Example 1, Example 4 and Table 1, the present application limits the modification effect of montmorillonite and gives full play to the structural characteristics of montmorillonite for adsorption and blocking;
[0118] In combination with Example 1, Example 5 and Table 1, the present application premixes cellulose nanocrystals with fillers to better exert the effect of nanocrystals, and the components in the system are more compatible and connected more tightly, so that the prepared TPU film has better performance;
[0119] In combination with Example 1, Example 6 and Table 1, the present application limits POSS to octaphenyl POSS, so that it is dispersed more evenly in the system, and utilizes the steric hindrance and electron-withdrawing characteristics of phenyl to enhance the connection effect with the surface negatively charged montmorillonite, and the prepared TPU film has better performance;
[0120] In combination with Example 1, Examples 7-11 and Table 1, the present application better exerts their functions by limiting the mass ratio of octaphenyl POSS to acid-modified montmorillonite, and the mass ratio of flame retardant filler to cellulose nanocrystals, and the internal structure of the prepared TPU film is more reasonable, and the performance of the prepared TPU film is better.
[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A flame retardant and anti-drip TPU film, characterized in that: The flame retardant and anti-drip TPU film comprises the following raw materials in parts by weight: 80-100 parts of TPU particles, 10-12 parts of flame retardant, 12-20 parts of flame retardant filler, and 0.01-1 part of cellulose nanocrystals. The flame retardant filler comprises cage-type polysilsesquioxane and acid-modified montmorillonite.
2. The flame retardant and anti-drip TPU film according to claim 1, characterized in that: The preparation steps of the acid-modified montmorillonite include: washing the montmorillonite, drying it, then adding it into a phosphoric acid solution with a volume concentration of 2-4%, stirring it evenly, filtering it, washing it, and drying it to obtain the acid-modified montmorillonite.
3. The flame retardant and anti-drip TPU film according to claim 1, characterized in that: The cage-type polysilsesquioxane is octaphenyl octasilsesquioxane.
4. The flame retardant and anti-drip TPU film according to claim 1, characterized in that: The flame retardant filler and the cellulose nanocrystals are premixed.
5. The flame retardant and anti-drip TPU film according to claim 3, characterized in that: The mass ratio of the octaphenyl octasilsesquioxane to the acid-modified montmorillonite is (2-2.3):
1.
6. The flame retardant and anti-drip TPU film according to claim 4, characterized in that: The mass ratio of the flame retardant filler to the cellulose nanocrystals is (15-20):
1.
7. The flame retardant and anti-drip TPU film according to claim 6, characterized in that: The mass ratio of the flame retardant filler to the cellulose nanocrystals is (16-17):
1.
8. A method for preparing the flame retardant and drip-resistant TPU film according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1: Dry the components of the raw materials separately, then weigh them according to weight and mix them evenly to obtain a mixture; S2: melt-blending, cooling, granulating and casting the mixed materials to obtain a flame-retardant and anti-drip TPU film.
9. The method for preparing the flame retardant and anti-drip TPU film according to claim 8, characterized in that: The melting temperature is 200-210°C, and the casting temperature is 180-200°C.
Citation Information
Patent Citations
Improvements in locks or latches for use with doors of motor vehicles, also applicable for other purposes
GB240984A
Cited By
Liquid-nitrogen-resistant ultralow-temperature thermoplastic composite film and preparation method thereof
CN122344400A